Benefits of exercise on cognitive impairment in alcohol use disorder following alcohol withdrawal - Zhen Lyu; Zhi‐Gang Gong; Min‐Xia Huang; Si‐Ping Xin; Mao‐Zhong Zou; Yu‐Quan Ding (FEBS Open Bio)
Although most cognitive impairments induced by prolonged alcohol consumption tend to improve within the initial months of abstinence, there is evidence suggesting certain cognitive deficits may persist. This study aimed to investigate the impact of aerobic exercise on learning and memory in alcohol use disorder (AUD) mice following a period of abstinence from alcohol. We also sought to assess the levels of monoamine neurotransmitters in the hippocampus. To this end, we established an AUD mouse model through a two‐bottle choice (sucrose fading mode and normal mode) and chronic intermittent alcohol vapor (combined with intraperitoneal injection) and randomly allocated mice into exercise groups to undergo treadmill training. Learning and memory abilities were assessed through the Morris water maze test and spontaneous activity was evaluated using the open field test. The levels of dopamine, norepinephrine, serotonin, and brain‐derived neurotrophic factor in the hippocampus were quantified using enzyme‐linked immunoassay (ELISA) kits. The findings reveal that after cessation of alcohol consumption, learning and memory abilities in AUD mice did not completely return to normal levels. The observed enhancement of cognitive functions in AUD mice through aerobic exercise may be attributed to restoring levels of monoamine neurotransmitters in the hippocampus, boosting brain‐derived neurotrophic factor (BDNF) concentrations, and facilitating an increase in hippocampal mass. These results offer empirical evidence to support aerobic exercise as a viable therapeutic strategy to alleviate cognitive deficits associated with AUD.